Combination therapies using an intratympanic polymer gel delivery system in the guinea pig animal model: A safety study. (May 2016) - Sidell, Douglas; Ward, Jonette A.; Pordal, Angad; Quimby, Carson; Nassar, Michel; Choo, Daniel I.
Abstract: Objectives: High dose antivirals have been shown to cause hearing loss when applied via the intratympanic route. The aim of this study was to determine if a combination therapy using dexamethasone (DXA) with either Cidofovir (CDV) or Ganciclovir (GCV), in solution or in PLGA-PEG-PLGA (PPP) hydrogel, is innocuous to the inner ear. Methods: Cytomegalovirus (CMV)-free guinea pigs were separated into four principal study groups and treated via intratympanic injection (IT) of CDV/DXA solution, CDV/DXA Hydrogel, GCV/DXA solution and GCV/DXA hydrogel. Hearing thresholds were evaluated with pretreatment ABR and post injection weekly ABRs for a total follow up of 28 days. Temporal bone tissue was harvested and stained with Hematoxylin and Eosin for histologic analysis. Results: ABR analysis revealed that GCV/DXA in solution and in hydrogel led to a mild hearing loss at days 7–21 but returned to baseline by day 28 When administered via PPP hydrogel, CDV/DXA demonstrated mild persistent hearing loss at 32 kHz at 28 days. An inflammatory response was identified in the cochlear specimen of the CDV/DXA/PPP hydrogel group, in concert with mild hearing loss, at days 21 and 28. Conclusion: Results of this study support the safe intratympanic use of higher concentrations of antivirals when combined with DXA, both in solution and when applied via PPP hydrogel.